Challenging Exceptionalism in Relation to Sources: Diplomatic Transitions and Archival Practices in the Context of the End of the French and British Empires in Africa - (:unkn) unknown (My University, 2020)
While several studies have shown the role of archives as channels of power and the influence of elites in the construction and interpretation of history, subaltern, postcolonial and decolonial studies have contributed to uncovering the marginalisation of colonised people in the history of empires and in the national history of former metropoles. Recently, the opening of new archives, and new research on archives as processes, spaces and objects, have generated a new connected history of French and British practices in the postcolonial transition in Africa. This article investigates the extent to which the exceptionalism of France’s African policy has been revised, and assesses the place given to the selection and management of the archival heritage in the ends of empire and the ongoing decolonisation in France and the United Kingdom. It concludes on the importance of community archives for the history and memory of the transfers of power, between state and non-state, national and transnational spheres.
Keywords: African Research